(untitled) (Modern education and development, 2025)
This article highlights the significance of incorporating play-based methods into English language teaching in preschool education. It explores how games, role-play, songs, and interactive activities not only make learning enjoyable for children but also enhance language acquisition, social interaction, and cognitive development. The article presents a comparative analysis of traditional and play-based approaches, emphasizing the effectiveness of playful learning environments.